KUALITAS LARVA HASIL HIBRIDISASI IKAN KERAPU MACAN (Epinephelus fuscogutattus) DAN IKAN KERAPU KERTANG (Epinephelus lanceolatus) DI BALAI PERIKANAN BUDIDAYA AIR PAYAU (BPBAP) SITUBONDO - Hermawan Gatot Priyadi; Taufik Hadi Ramli; Septiana Putri; Ayu Amalia Rizki; Agung Anggoro Doni (Universitas Muhammadiyah Gresik, 2024)
The cantang grouper is a hybrid of the tiger grouper and the cantang grouper. The canting grouper has qualities that make it desirable for further development, including rapid growth, disease resistance, and environmental tolerance. This research aims to determine the embryological process and the hatching rate (HR) results. This research was carried out from September 1 to December 30, 2023, at Balai Perikanan Budidaya Air Payau (BPAP) Situbondo. The method used in this research is a descriptive method obtained from primary data and secondary data. The quality of larvae from the hybridization of tiger grouper fish (Epinephelus fuscogutattus) and kertang grouper fish (Epinephelus lanceolatus) was obtained through embryology and hatching rate observations. This research concludes that rearing hybridized canting grouper larvae includes several processes: egg development, egg harvesting, preparation of rearing tanks, egg stocking, hatching rate, observation of larvae, feeding management, water quality management, and disease management. The Hatching Rate (HR) percentage obtained was 82%, which is classified as high quality according to SNI standards.